Stokes flow analogous to viscous electron current in graphene - Jonathan Mayzel (Nature Portfolio, 2019)
Viscous electron flow in graphene has been shown to exhibit vortices. Here the authors report analogous vortices in viscous fluid flow through a narrow channel making the presented fluidic system an attractive setup for quantative measurements which are otherwise hard to perform with viscous electron flow.